EVALUASI PENGELOLAAN PENYIMPANAN SEDIAAN FARMASI DI GUDANG INSTALASI FARMASI RSIA IBUNDA PELAIHARI - Ilahi, fitrah shafran; Tia Nor Aprilia; Abdul Mahmud Yumassik; Amaliyah Wahyuni (Jurnal Insan Farmasi Indonesia, 2023)
Drug storage in hospital pharmacy installations is a guarantee of the feasibility of drugs received by the hospital before being distributed to patients.Â  pharmaceutical preparations used by the pharmaceutical installation warehouse at RSIA Ibunda Pelaihari based on the quality standards of the Minister of Health regulation number 72 of 2016 concerning service standards in hospitals. The research method uses a qualitative observational method, the research instrument used in data collection is an observational sheet. The results showed that the storage of pharmaceutical preparations in the pharmaceutical installation warehouse of RSIA Ibunda Pelaihari obtained a figure of 92% which was included in the good criteria based on the results of the calculation of the observation sheet carried out in the pharmaceutical installation warehouse of RSIA Ibunda Pelaihari by showing parts that were in accordance with the Permenkes standard number 72 of 2016, namely storage components, storage system, storage method. While as many as 8% that have not met the standards are the storage requirements and storage equipment. The storage of pharmaceutical preparations in the pharmaceutical warehouse of RSIA Ibunda Pelaihari has met the standards of Permenkes number 72 of 2016 with a percentage of 92% which is in the good category.